Pelatihan Kepemimpinan: From Organization to Become the Best Leader - Prasetyo, Johan Hendri; Wiharso, Gani; Fabrianto, Luky; Safitri, Rizky Ade (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The community service activity holds a crucial urgency in raising awareness about the significant role of youth in village development, particularly in Ragunan District. By organizing the